Optimasi Pupuk Organik Cair Dan Npk Terhadap Beberapa Sifat Kimia Tanah Dan Hasil Jagung Di Lahan Tercemar Limbah Clarifier - Mulyana, Muhammad Agus; Sofyan, Emma Trinurani; Suryatmana, Pujawati (Jurnal Agrotek Indonesia, 2018)
Degradation of rice fields ecosistem from industrial waste contamination has caused harmful impact for farming sustainability and developing crop production. This study aimed to investigate the effect of various treatment of NPK and Liquid Organic Fertillizer towards several chemical compound in the soil and Vegetatif and generative Growth of Sweet Corn (Zea mays) in clarifier contaminated rice fields from industrial waste. The experiment was conducted in the contaminated clarifier ricefield of PT PUPUK KUJANG CIKAMPEK from June to August 2017. Randomized block design with nine single treatment, that is A = 0 NPK and 0 ml/L POC, B = 1 NPK and 0 ml/L POC, C = 1 NPK and 2,5 ml/L POC, D = 1 NPK and 5 ml/L POC, E = 1 NPK and 7,5 ml/L POC, dan F = 1 NPK and 10 ml/L POC, G = 3/4 NPK and 5 ml/L POC, H = 1/2 NPK and 5 ml/L POC, I = 0 NPK and 5 ml/L POC each with three replicates was used as experimental design in this research. The result showed that the application NPK and Liquid Organic fertilizer has significant effect on increasing several chemical compound in the soil and Vegetatif and generative Growth of Sweet Corn (Zea mays). Keywords : NPK, Liquid Organic Fertillizer